Pergeseran Mustahik Zakat Mal Dalam Konsep Sabilillah Dari Fiqh Klasik ke Fiqh Kontemporer - Muhammad; Mahfida Inayati; Nurul Zainab (STAI Terpadu Yogyakarta, 2024)
Zakat is worship that has two side dimensions. On the one hand zakat is a worship that functions as a purification of property (tazkiyyah li al-mâl) on the owner, on the other hand zakat contains high social significance. Those who are entitled to receive zakat (mustahik zakat) have been established by Allah Almighty in the Qur'an and the classification is clear, only the sabîlillah group is considered less clear and less firm because it has many understandings and interpretations both according to classical and contemporary scholars. The type of research used is library research using the comparative approach method. As for the primary data, namely Fiqh as-Sunnah by Sayid Sabiq; Fiqh al-Zakâh by Yûsuf al-Qardhawî; and Al-Fiqh al-Islâmi wa Adillatuhu by Wahbah Az-Zuhaily; as well as secondary data, namely other literature relevant to the research material. After going through analysis, several findings were obtained, First: that according to classical fiqh scholars the concept of sabîlillah is not allowed to give zakat for the sake of the common good and benefit such as erecting bridges, building mosques, schools, repairing roads, and others. Second: the concept of Sabîlillah according to Contemporary fiqh namely Prof. Dr. Sayyid Sabiq, and Dr. Yûsuf al-Qardhâwi is that they extend the concept of sabîlillah not only to people who fight on the battlefield, but all goodness that has maslahah value and for social interests. Third: factors that influence the shift in the concept of sabîlillah as mustahik zakat mâl so that the target of zakat can be implemented and realized properly in accordance with the present.